2011
DOI: 10.3109/09513590.2011.588753
|View full text |Cite
|
Sign up to set email alerts
|

The role of prostaglandin E 2 in endometriosis

Abstract: Endometriosis is a leading cause of infertility in women of reproductive age. It involves the occurrence of endometrial tissue outside the uterine endometrium, mainly in the peritoneal cavity. Prostaglandin E(2) is up regulated in the peritoneal cavity in endometriosis and is produced by macrophages and ectopic endometrial cells. This prostaglandin is involved in the pathophysiology of the disease and elicits cell signals via four receptor types. Prostaglandin E(2) increases estrogen synthesis by up regulating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 74 publications
0
51
0
2
Order By: Relevance
“…Thus, STAR and aromatase are the key steps in estrogen production. They are normally absent in eutopic endometrium, but found at high levels in patients with endometriosis (Sacco et al, 2012).…”
Section: Sex Steroid Hormonesmentioning
confidence: 99%
“…Thus, STAR and aromatase are the key steps in estrogen production. They are normally absent in eutopic endometrium, but found at high levels in patients with endometriosis (Sacco et al, 2012).…”
Section: Sex Steroid Hormonesmentioning
confidence: 99%
“…In endometriosis patients, there is a significant increase in PGE2 in peritoneal cavity and eutopic endometrium [166,167]. PGE2 is involved in pathogenesis of endometriosis and affects oocyte maturation, ovulation, and fertilization.…”
Section: Targeting Inflammation For Treatment Of Endometriosis-assmentioning
confidence: 99%
“…PGE2 is involved in pathogenesis of endometriosis and affects oocyte maturation, ovulation, and fertilization. PGE2 exerts its biological functions via four G protein-coupled receptors EP1, EP2, EP3, and EP4 [166]. Both EP2 and EP4 act through Gs-coupled effects, while EP1 acts via Gq-coupled pathway [166].…”
Section: Targeting Inflammation For Treatment Of Endometriosis-assmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Sacco et al reported the efficacy of progestin therapy on prostaglandin E 2 (PGE 2 ) involved in endometriosis (5). According to their report, PGE 2 is produced in macrophages and ectopic endometrium in patients with endometriosis, causing up-regulation within the peritoneal cavity and increasing estrogen synthesis through up-regulation of steroidogenic acute regulatory protein (StAR) and aromatase.…”
Section: Progestin Therapy For Endometriosismentioning
confidence: 99%